Assessing Students' Higher-Order Thinking Skills In Reading Comprehension - Hamma, Syah Ibi; Nappu, Syamsiarna; Akib, Erwin (Institut Agama Islam Negeri Palopo, 2023)
This research aimed to find out the score of students’ higher-order thinking skills (HOTS) in Reading Comprehension and the challenges faced by the students when solving HOTS. This research used a quantitative descriptive design. The data were obtained by using tests and questionnaires. The subjects of this research were 22 students who studied in the Twelfth Grade IPA 1 in SMA Pesantren IMMIM Makassar. By definition, Higher-Order Thinking is divided into 3 Categories which were Higher-Order Thinking As Transfer (C4), Higher-Order Thinking as Critical Thinking (C5), and Higher-Order Thinking as Problem Solving (C6). The students answered the test and the questions were at the HOTS level. In challenges, this research investigated the challenges faced by the students when solving HOTS by analyzing the questionnaire. The findings of this research revealed that the score of students’ HOTS was 64,54% which was considered Good, It shows that students scored Higher-Order Thinking as Transfer (C4) was 81,8%, while Higher-Order Thinking as Critical Thinking (C5) was 54,5% and Higher-Order Thinking as Problem Solving (C6) was 9.1%, and as for the challenges faced by students when solving HOTS was 16.63% students facing difficulties in understanding the Meaning of Word (C4), 27.72% facing difficulties in Making Inferences (C5) and 28.81% students facing difficulties in Determining the Main Idea (C6) when solving HOTS Questions. It can be concluded that the student’s Higher-Order Thinking as Transfer (C4) was Excellent, Higher-Order Thinking as Critical Thinking (C5) was good and Higher-Order Thinking as Problem-Solving was Poor, and the challenges that the students faced when solving HOTS Questions were mostly determining the main idea and making inference.